UNA SEPULTURA SINGULAR DEL CABECICO DEL TESORO. VERDOLAY, LA ALBERCA, MURCIA - García Cano, José Miguel (Anales de Prehistoria y Arqueología, 1987)
This piece of work is a thoroughgoing study on tomb remains n.O 549 of the Cabecico del Tesoro Iberian necrópolis at Verdolay, La Alberca (Murcia), whose specific relevance lies in its funerary paraphernalia inclusing a perfume pot the TALCOTT type, a Greek type of vase rarely to be found in the Iberian Peninsula. Moreover it tries to ascertain whether those paraphernalia were meant to have a ritual aim; the conclusion being that no firm evidence has been reached connecting this gear with any specific ritual. The tomb is datable from the Vth Century B. C. or very early IV th Century B. C.